Tipos de espermatogonios en "Tepezcuintle" (Cuniculus paca). Estudio ultraestructural - Ureña, Francisco; Bolaños, Rodolfo; Rojas, Nancy; Suárez, Roberto; Quesada, Rafael (Revista de Biología Tropical, 1988)
Ultraestructural studies of different types of espermatogonia by thin section techniques and tranamission electron microscopy showed that Cuniculus paca has two types of Type A spermatogonia (A-0 and A-1). Samples were taken at different stages of the cycle in the seminiferous tubule epithelium presented a similar pattern as those of other rodents. Type B spermatogonia are similar to those of the rat, the difference being that the heterochromatic zones are larger and more numerous. Both characteristics differentiate them from preleptotenic spermatocytes.